Dry matter intake prediction of steers and heifers in the feedlot effect of initial weight on dry matter intake - Koknaroglu, H.; Loy, D. D.; Hoffman, M. P. (2008)
Close-out information, generated by the Iowa State University Feedlot Performance and Cost Monitor-ing Program submitted from January 1988 through December 1997 by Iowa cattle producers to IowaState University, was examined to determine the effect of initial weight on dry matter intake (DMI) ofsteers and heifers in the feedlot. Close-out information consisting of 2445 pens of steers and 965 pensof heifers included information on start and end dates, cattle per pen, sex, housing type, days on feed,initial and sale weight, feed conversion (FC), proportion of concentrate, average daily gain (ADG),percent death loss, feed cost and total cost per 45.35 kg gain, breakeven sale price, non-feed variablecost, non-feed fixed cost and corn price. Daily DMI was not provided but was calculated as DMI = ADGx FC. Regression model included initial weight and, thus, DMI was regressed on initial weight forsteers, heifers and combination of both. When the model was applied separately for steers, heifersand including both sexes, DMI prediction for steers was found as DMI = 5.81 + 0.0125*Initial weight(n=2445, r2=0.41), whereas DMI prediction for heifers was found as DMI = 5.03 + 0.0144*Initial weight(n=965, r2=0.38). When steers and heifers were combined, DMI prediction was found as DMI = 5.49 +0.0133*Initial weight (n=3410, r2=0.43). These results are similar to those obtained by NRC (1996)where DMI = 4.54 + 0.0125*Initial weight. These prediction models predict average feed intake through-out a feeding period and implies that initial weight of cattle is related to average DMI during a feedingperiod. Slope for heifers was higher than that of steers, implying that heifers had a greater increase inDMI throughout a feeding period per unit of initial body weight.
Keywords: Cattle feeding and feeds